The effect of nutritional status on the menstrual cycle and duration of menstruation in active pre-clinical female students of the 2023 intake at the UMI Faculty of Medicine - Iis Nurafifah Putri Mas’ud; Arni Isnaini Arfah; A.Husni Esa Darussalam; Nesyana Nurmadilla; Rizki Amalia (Jurnal EduHealth, 2025)
Women with excess or deficiency nutritional status can cause decreased hypothalamic function so that it does not provide stimulation to the anterior pituitary to secrete FSH (Follicle Stimulating Hormone) and LH (Leuteinizing Hormone). In women who experience excess nutrition, there is an increase in high estrogen hormones that provide negative feedback on the production of GnRH (Gonadotropin Hormone) through the secretion of inhibitor proteins that can inhibit the work of the anterior pituitary to produce FSH. The purpose of this study was to determine the effect of nutritional status on the menstrual cycle of active pre-clinical students of Class of 2023 at the Faculty of Medicine, UMI. Using the cross-sectional method, and bivariate data analysis using the Chi Square test . The results of the study stated that nutritional status affects the menstrual cycle, and nutritional status affects the duration of menstruation.